The Effects of Economic Growth, The Minimum Wage, and the Unemployment Rate on the Number of People Living in Poverty in East Java, 2020–2024 - Anggraeni Rahmasari; Fatihul Khoir; Indah Noviandari; Adisty Amanda Putri (Green Publisher Indonesia, 2026)
This study aimed to analyze the partial and simultaneous effects of economic growth, minimum wages, and unemployment rates on the number of people living in poverty in East Java Province from 2020 to 2024, as well as to identify the dominant variables influencing poverty levels. This research employed a quantitative approach using secondary data obtained from the Central Statistics Agency of East Java Province. The data consisted of information related to the number of people living in poverty, economic growth, minimum wages, and unemployment rates during the 2020–2024 period. The results of the partial testing (t-test) showed that the economic growth variable, measured by Gross Regional Domestic Product (GRDP), did not have a significant effect on the number of people living in poverty in East Java Province during the study period, with a significance value of 0.508, which was greater than the 0.05 significance level. In contrast, the minimum wage variable (Upah Minimum Provinsi or UMP) and the open unemployment rate variable (Tingkat Pengangguran Terbuka or TPT) had significant effects on poverty levels, with significance values of 0.017 and 0.007, respectively, which were below the 0.05 threshold. Meanwhile, the results of the simultaneous testing (F-test) indicated that economic growth (GRDP), minimum wages (UMP), and open unemployment rates (TPT) collectively had a significant effect on the number of people living in poverty in East Java Province during the 2020–2024 period, with a significance value of 0.029, which was lower than 0.05.